ИЗУЧЕНИЕ МИГРАЦИОННЫХ МАРШРУТОВ И МЕСТ ЗИМОВОК ХИЩНЫХ ПТИЦ КОСТАНАЙСКОЙ ОБЛАСТИ - Брагин, Е.А. (My University, 2019)
Аннотация В данной работе приводятся результаты исследования миграционных маршрутов и мест зимовок орла-могильника (Aquila heliaca), орлана-белохвоста (Haliaeetus albicilla), кобчика (Falco vespertinus), степного луня (Cyrcus macrourus) и степного орла (Aquila nipa- lensis), гнездящихся в Костанайской области. Аbstract This paper presents the results of a study of migration routes and wintering grounds of the Imperial eagle Aquila heliaca, White-tailed eagle Haliaeetus albicilla, Red-footed falcon Falco vespertinus, Pallid Harrier Cyrcus macrourus and Steppe eagle Aquila nipalensis nesting in Kosta- nay region.
Study of the migratory routes and wintering areas of the birds of prey of the Kostanay region E.A. Bragin
Keywords: хищные птицы; миграции; миграционный маршрут; область зимовок; Костанайская область; birds of prey; migrations; migratory routes; wintering area; Kostanay region